TELAAH THE HOLY QUR’AN KARYA ABDULLAH YUSUF ALI - Sulaiman Ibrahim (Hunafa: Jurnal Studia Islamika, 2010)
This article deals with The Holy Qur’an, a book of translation and of a quranic exegeses written by  Abdullah Yusuf Ali. This book becomes popular since it not only uses international language (English), but also possesses its own characteristics which make it different from other books of  exegeses.  The Holy Qur’an is so dominant in its sufistical commentary that it employes esetoric hermeneutics over the symbols existing in the Qur’an. In addition, this book employs lexical, grammatical, contextual, and social-cultural meanings that convey message that the translator depends on the standard language of the Qur’an. Abdullah Yusuf Ali obey does not the literal meanings of the verses, but he puts stongger emphases on its spiritual meanings.Kata Kunci: The Holy Qur’an, Abdullah Yusuf Ali, kitab tafsir